Redescription of the eagle rays Myliobatis hamlyni Ogilby, 1911 and M. tobijei Bleeker, 1854 (Myliobatiformes: Myliobatidae) from the East Indo-West Pacific - White, William T.; Kawauchi, Junro; Corrigan, Shannon; Rochel, Elisabeth; Naylor, Gavin J.p. (Zootaxa, 2015)
The eagle rays Myliobatis hamlyni Ogilby, 1911 and Myliobatis tobijei Bleeker, 1854 are redescribed based on museum specimens and new material from Australia, Indonesia, the Philippines, Taiwan and Japan. These two species are closely related to Myliobatis aquila (L.) from the eastern Atlantic and can be distinguished from each other by a combination of their coloration, meristics, depth preferences and subtle morphometric characters. Myliobatis hamlyni was previously considered to be an Australian endemic, but its distribution is herein extended northward to Taiwan and Okinawa. Myliobatis tobijei was considered to occur southwards from Japan to Indonesia, but its distribution is herein restricted to the western North Pacific, primarily Japan.